Potential Down-Regulation of Salivary Gland AQP5 by LPS via Cross-Coupling of NF-κB and p-c-Jun/c-Fos - Yao, Chenjuan (American Society for Investigative Pathology, 2010)
The mRNA and protein levels of aquaporin (AQP)5 in the parotid gland were found to be potentially decreased by lipopolysaccharide (LPS) in vivo in C3H/HeN mice, but only weakly in C3H/HeJ, a TLR4 mutant mouse strain. In the LPS-injected mice, pilocarpine-stimulated saliva production was reduced by more than 50%. In a tissue culture system, the LPS-induced decrease in the AQP5 mRNA level was blocked completely by pyrrolidine dithiocarbamate, MG132, tyrphostin AG126, SP600125, and partially by SB203580, which are inhibitors for IκB kinase, 26S proteasome, ERK1/2, JNK, and p38 MAPK, respectively. In contrast, the expression of AQP1 mRNA was down-regulated by LPS and such down-regulation was blocked only by SP600125. The transcription factors NF-κB (p65 subunit), p-c-Jun, and c-Fos were increased by LPS given in vivo, whereas the protein-binding activities of the parotid gland extract toward the sequences for NF-κB but not AP-1–responsive elements present at the promoter region of the AQP5 gene were increased by LPS injection. Co-immunoprecipitation by using antibody columns suggested the physical association of the three transcription factors. These results suggest that LPS-induced potential down-regulation of expression of AQP5 mRNA in the parotid gland is mediated via a complex(es) of these two classes of transcription factors, NF-κB and p-c-Jun/c-Fos.